Planetary system detection by estimating the covariance of coronagraphic lucky images. Issue 3 (15th July 2019) - Cagigas, Miguel A; Cagigal, Manuel P; Valle, Pedro J; Canales, Vidal F; Fuentes, Antonio; López, Roberto
ABSTRACT: In this paper, we review two different methods to increase image contrast and propose the combination of both to detect faint companions surrounding a host star. Coronagraphy allows us to block light coming from the host star so that the residual star light can be reduced by several orders of magnitude. On the other hand, estimating the Covariance of Lucky Images (COELI) is a proven method to detect faint companions from ground-based telescope images. The dynamic range of the detection camera limits this technique. Hence, the application of COELI to coronagraphic images may increase the magnitude range of the detectable companions. COELI only requires the existence of a reference, which can be obtained using an existing stellar companion or using a coronagraphic mask designed to create a faint image of the host star. We provide an analysis of the combination of the techniques by processing coronagraphic images obtained by the William Herschel Telescope.